(untitled) (Journal of Dhaka National Medical College & Hospital, 2025)
Background: Volar Barton fractures represent a specific type of intra-articular fracture, resulting from shear pressures that lead to the displacement of the volar lips of the distal radius. Volar Barton fractures are uncommon and exhibit significant instability. This type of fracture is almost always associated with volar subluxation of the radiocarpal joint. The results of conservative treatment for volar Barton fractures are often disappointing and associated with various complications. Volar Barton fractures of the distal radius generally require surgical fixation to achieve the best possible outcomes. Objectives: To assess the functional results of volar Barton fractures in active adults who have undergone open reduction and internal fixation with a volar locking plate. Methods: This prospective study was conducted at various private hospitals in Dhaka and Narayanganj from January 2019 to December 2022. We analyzed the outcomes of twenty-two cases of volar Barton fractures, which were managed through open reduction and internal fixation utilizing a volar locking plate. The patients were assessed at regular intervals, with the final follow-up occurring one year later for each individual. Results: This study comprised the open reduction and internal fixation utilizing a volar locking plate in a group of 22 individuals diagnosed with volar Barton fractures. Throughout the course of one year, all patients underwent monitoring to evaluate the outcomes of their treatment. Every fracture has been successfully fixed. The average time for fracture union was found to be 8.5±2.5 weeks. By the end of the follow-up period, every patient successfully attained the necessary and satisfactory range of motion. Based on the Modified Mayo Wrist Score, a remarkable 54.55% of patients achieved excellent functional outcomes, while 40.91% exhibited good outcomes. It is recommended that open reduction and internal fixation with a volar locking plate serves as a highly effective treatment approach for volar Barton fractures in active adults. Conclusions: Open reduction and internal fixation with a volar locking plate is a trustworthy treatment option with promising results for volar Barton fractures of the distal radius in active adult patients J. Dhaka National Med. Coll. Hos. 2025; 31 (01): 21-24